Assessing the Social Validity of the SAFMEDS Strategy From the Perspective of Teachers and Children - Owen, Kaydee; Watkins, Richard C.; Beverley, Michael; Hughes, J. Carl (Frontiers in Education, 2021)
The Say-All-Fast-Minute-Every-Day-Shuffled (SAFMEDS) strategy promotes fluency across several skills and contexts. However, few studies have reported the social validity key stakeholders associate with using the strategy in schools. Assessing social validity may provide us with some insight into factors that may affect engagement, implementation fidelity, and persistent use of the intervention after the termination of a research study. Study 1 details the findings from a survey completed by teachers who have used the strategy in their schools (N = 55). Using thematic analysis, we identified three themes: (1) factors that promote and limit progress, (2) confidence, and (3) inherent advantages of the SAFMEDS strategy. These themes encapsulate teachers experiences of implementing the strategy under the real-word conditions of the classroom, and the accompanying advantages and potential challenges they face. Within study 2, we discuss themes arising from interviews with children (N = 26) about their views and experiences of using the SAFMEDS strategy. These children had used the strategy with their teacher for one academic year to promote fast and accurate recall of arithmetic facts. Analysis of these transcripts revealed five further themes relating to children’s engagement with the strategy: (1) enjoyment, (2) data, (3) sense of achievement, (4) skills, and (5) home use. Collectively these themes have potential impact with regards to future training and support models for the SAFMEDS strategy.